2007
DOI: 10.1111/j.1540-8159.2007.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Atrial Pacing: A Useful Technique During Slow Pathway Ablation

Abstract: Rapid atrial pacing during radiofrequency catheter ablation of the slow pathway is a safe alternative approach to ensure normal AVN function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Rapid atrial pacing is commonly practiced during EPS and provides useful information regarding AV node status 14 . A critical parameter obtained from atrial pacing is WCL, defined as the atrial pacing period at which AV nodal conduction degenerates to Wenckebach Rhythm 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid atrial pacing is commonly practiced during EPS and provides useful information regarding AV node status 14 . A critical parameter obtained from atrial pacing is WCL, defined as the atrial pacing period at which AV nodal conduction degenerates to Wenckebach Rhythm 15 .…”
Section: Discussionmentioning
confidence: 99%
“…[2] SP modification, rather than the fast pathway method, is now the preferred approach to ablate AVNRT because of the lower incidence of complications. [3] The AV node is a relatively large structure and the belief is that the fast pathway alone is sufficient to maintain the AV conduction for the remainder of the patient's life, after blocking the SP.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Retrograde conduction block during JR or development of rapid JR are significant predictors of AVB in patients undergoing SP ablation. Previous studies have suggested several strategies to avoid AVB including transient discontinuation of energy delivery with the development of JR, and multiple repeat ablations with progressively longer durations ≤30 s. 8 Another method proposed by Liberman et al 9 argued that rapid atrial pacing during ablation could be used to ensure intact anterograde conduction. However, JR that is slightly faster than the pacing CL may be difficult to identify in this setting and retrograde conduction cannot be assessed during JR.…”
Section: Discussionmentioning
confidence: 99%